TEMPO’S POLITICAL STANCE REPRESENTATION TOWARD KPK IN INSTAGRAM ACCOUNT OF TEMPODOTCO: AN ATTITUDE SYSTEM APPROACH (REPRESENTASI SIKAP POLITIK TEMPO TERHADAP KPK DALAM AKUN INSTAGRAN TEMPODOTCO: ANCANGAN SISTEM PERILAKU) - Devi Nailis Yusnia (Metalingua: Jurnal Penelitian Bahasa, 2021)
Abstract : This study aims at investigating Tempo Media’s political stance representation toward KPK in the notion whether Tempo Media support the revision of KPK laws and the election of the new Head of KPK, or in contrast, oppose them in the news they posted in their instagram account, ‘tempodotco’, during 28-30 September 2020.  To reveal the stance, the writer uses attitudinal approach in the appraisal framework as well as analyzing linguistic features that represent stance. Further, this study applied descriptive qualitative methods. The result suggests that grammatical and lexical choices are essential in articulating stance. In addition, this study shows the high use of negative judgment and negative appreciation to evaluate the stance object. In contrast, the affect attitude is barely found in this study. At the end, the overall result yields that Tempo Media opposes both the revision of KPK law and the election of new Head of KPK.